2020
DOI: 10.1038/s41598-020-66884-z
|View full text |Cite
|
Sign up to set email alerts
|

A smart switching system to enable automatic tuning and detuning of metamaterial resonators in MRI scans

Abstract: We present a radio-frequency-activated switching system that can automatically detune a metamaterial resonator to enhance magnetic resonance imaging (MRI) performance. Local sensitivity-enhancing metamaterials typically consist of resonant components, which means that the transmitted radio frequency field is spatially inhomogeneous. The switching system shows for the first time that a metamaterial resonator can be detuned during transmission and tuned during reception using a digital circuit. This allows a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Compared to the existing solutions for detunable MRI MTMs 29,30 , our smart metasurfaces exhibit a larger penetration depth and slower decrease of the SNR enhancement factor while maintaining a similar or even better SNR enhancement performance. The results clearly show that the SNR in MRI can be substantially improved with smart yet thin MTMs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to the existing solutions for detunable MRI MTMs 29,30 , our smart metasurfaces exhibit a larger penetration depth and slower decrease of the SNR enhancement factor while maintaining a similar or even better SNR enhancement performance. The results clearly show that the SNR in MRI can be substantially improved with smart yet thin MTMs.…”
Section: Discussionmentioning
confidence: 98%
“…So far, only very few tunable MRI MTMs have been presented in general, and there are even less proposals that achieve the tuning depending on the imaging phase without the need of active intervention. 29,30 Non-linear MTMs 29 are introduced as a promising solution since they can be sensitive to the imaging phase but also MRI-compatible additional battery-powered electronic sensing circuits 30 can be used to take care of the state-switching. However, in all known cases the suggested MTMs are bulky structures (such as helix-shaped configurations or 3d arrangements of conducting bars), putting patient-specific design, patient comfort, and flexible or conformal manufacturing benefits beyond reach.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have been conducted to realize the nonlinear properties of metasurfaces to solve this problem. [ 24,34 ] Although a nonlinear planar metasurface was suggested to avoid interference in the transmitting field, [ 24 ] it has a few drawbacks. The proposed “intelligent metasurface” was illustrated by the proximal image quality (SE image of an onion) in a qualitative rather than quantitative manner, that is, from the B1+ field or the real FA.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested detuning the metasurface in the transmitting period, but their design was planar in configuration. [ 34 ] Moreover, the design of the switching system was too complicated, and its nonlinearity could not be controlled and was not quantitatively characterized from the B1+ field.…”
Section: Discussionmentioning
confidence: 99%
“…This effect locally increased the transmit efficiency and Signal-to-Noise Ratio (SNR) of the BC. The water-filled wire MS was followed by several modifications proposed for the same type of resonant focusing operation [21,22,23,24,25,26,27,28], and some alternative MS-based coupled resonators were proposed (e.g., [29,30]).…”
Section: Introductionmentioning
confidence: 99%